Analysis of the Role of Customer Engagement in Mediating the Effect of Video Information Quality and Perceived Authenticity on Purchase Intention: A Study on Kick Avenue TikTok - Nilna Muna; I Putu Indra Wiguna (LP2M IAIN Palopo, 2026)
The rapid development of social commerce on TikTok has changed consumer purchasing behavior in Indonesia, but the mediating role of customer engagement between video information quality, perceived authenticity, and purchase intention remains underexplored, especially for premium sneaker brands like Kick Avenue. This study aims to analyze the mediating effect of customer engagement on the influence of Video Information Quality (VIQ) and Perceived Authenticity (PA) on Purchase Intention (PI). Using an explanatory quantitative design with a cross-sectional online survey (n=240 purposive samples of TikTok users aged ≥17 who viewed Kick Avenue content), data were collected through a 20-item Likert-4 scale questionnaire adapted from validated sources and analyzed with SEM-PLS on SmartPLS 4.0. The results showed significant direct effects (VIQ→PI β=0.386; PA→PI β=0.450; CE→PI β=0.394, all p<0.001) and partial mediation (VIQ→CE→PI β=0.174; PA→CE→PI β=0.107, p<0.001), explaining 69.2% of the variance in CE and 41.8% of the variance in PI (Q²=0.821). In conclusion, quality and authentic video content drives engagement to increase purchase intention, providing guidance for TikTok strategies for retailers.